Phytocompounds from Indonesia Medicinal Herbs as Potential Apelin Receptor Agonist for Heart Failure Therapy: An In-silico Approach - Muhamad Rizqy Fadhillah; Wawaimuli Arozal; Muhammad Habiburrahman; Somasundaram Arumugam; Heri Wibowo; Suci Widya Primadhani; Aryo Tedjo; Surya Dwira; Nurul Gusti Khatimah (International Journal of Technology)
Heart failure is still a global health problem that demands new pharmacological treatments. The Apelin Receptor (APR), a class A (rhodopsin-like) G-Protein Coupled Receptor (GPCR), is one of the cell membrane receptors that potentially become a specific target of heart failure therapy when activated. However, no clinically approved drugs target APR. Phytochemical compounds from Indonesian herbs have become readily available for discovering novel apelin agonists. This study investigates bioactive phytochemicals from ten Indonesian medicinal herbs using computer-aided drug design (CADD) to predict ligand-receptor interactions via molecular docking and bioactivity prediction through machine learning. The selected herbs include Andrographis paniculata, Centella asiatica, Zingiber officinale, Curcuma longa, Curcuma domestica, Morinda citrifolia, Guazuma ulmifolia, Orthosiphon stamineus, Moringa oleifera, and Garcinia mangostana. Their pharmacokinetic and physicochemical profiles were also assessed using web-based predictions. Active metabolites were sourced from the Knapsack Database. Molecular docking using Molegro Virtual Docker assessed binding energy, with more negative MolDockScores indicating stronger interactions. Gambogic acid (-155.1 kJ/mol) from Garcinia mangostana and Procyanidin B2 (-154.5 kJ/mol) from Guazuma ulmifolia exhibited stronger binding than the APR agonist, Azelaprag (-149.9 kJ/mol). This study showed that Gambogic acid, Procyanidin B1, and Procyanidin B2 may predict excellent half maximal effectivity (EC50) against apelin receptors, despite their unideal lipophilicity-ligand efficiency (LELP). Gambogic acid demonstrated favorable pharmacokinetic properties: good bioavailability, minimal blood-brain barrier penetration, no cytochrome P450 (CYP) enzyme interactions, and low toxicity. The study concluded that all five selected compounds exhibited strong interactions and bioactivity as APR agonists, supporting the need for further validation through in-vitro studies.